2019
DOI: 10.1111/ane.13112
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in the quality of stroke care in Sweden

Abstract: Time of admission affects the quality of care across a wide range of clinical presentations including acute stroke. [1][2][3][4][5][6][7][8][9][10][11] In particular, a recently published meta-analysis revealed increased short-term mortality and disability at discharge in stroke patients who had presented off-hours. 12 However, less is known about the underlying causes of these effects. 13,14 A recent study on general emergency admissions found that the magnitude of the weekend effect was significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
0
10
1
Order By: Relevance
“…The study of the Swedish Stroke Registry noted that patients admitted in night time had a lower 30 and 90 day survival than those in daytime. That finding was explained by that door-to-needle time within 30 minutes was less likely during nighttime than daytime [ 26 ]. Interestingly, they found that university hospitals were more resilient to temporal variation- this could be applied to our study- than specialized non-university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the Swedish Stroke Registry noted that patients admitted in night time had a lower 30 and 90 day survival than those in daytime. That finding was explained by that door-to-needle time within 30 minutes was less likely during nighttime than daytime [ 26 ]. Interestingly, they found that university hospitals were more resilient to temporal variation- this could be applied to our study- than specialized non-university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in treatment, stroke is still the third leading cause of death, following cancer and heart disease . Worldwide, 78% of all stroke events are caused by cerebral infarctions and 22% by a haemorrhage, while, in Western Europe, approximately 85% of all stroke events have an ischaemic origin . Today, stroke is also the leading cause of neurological long‐term disability and almost 30% of stroke survivors are dependent in activities of daily life one year after a stroke .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the impact on door to needle, door to groin puncture, short‐term hospital mortality, and long‐term clinical outcomes in patients presenting to the hospital during working and nonworking hours. A negative “off‐hours effect” in many of these studies has been attributed to less experienced physicians at night, fewer available staff, and lack of advanced imaging availability 4,5 . However, this effect was not detected in patients presenting to CSCs, likely attributable to higher quality of care and efficient stroke protocols 5 .…”
mentioning
confidence: 99%
“…A negative "off-hours effect" in many of these studies has been attributed to less experienced physicians at night, fewer available staff, and lack of advanced imaging availability. 4,5 However, this effect was not detected in patients presenting to CSCs, likely attributable to higher quality of care and efficient stroke protocols. 5 As treatment of LVOs advances, attempts to improve efficiency and reduce costs have been made across the stroke systems of care.…”
mentioning
confidence: 99%
See 1 more Smart Citation